Good Governance Overview: Public Satisfaction Related to Medan Berkah Program Using Monte Carlo Method in Waste Management of Medan City - Srifauzi, Aulia; Batubara, Rini Oktari; Ardiansyah, Yuda; Saputra, Dede Ardi (Journal of Islamic World and Politics, 2024)
In 2023, Medan City won the Adipura award in the metropolitan city category after being declared one of the dirtiest cities at the end of 2019. This achievement aligns with the Medan Berkah Collaboration program promoted by the Medan City Government, which is part of the effort to make Medan a sustainable, clean, and conducive city. The success of the city government in achieving this goal largely depends on the extent to which problems can be addressed and viewed positively by the public. This research uses the concepts of good governance and SDGs. Good governance creates an ecosystem that enables partnerships between government, society, and the private sector to achieve SDG targets jointly. Good governance, in the view of Islamic law, prioritizes the interests and benefits of humans with a system of regulation, control, and implementation in a country or region. Then, the author uses the Monte-Carlo method to predict the level of public satisfaction with handling waste management and waste as a consideration for the government in formulating further policies. This research is qualitative, and the data collection methods are observation, documentation, FGDs, and interviews. Data was taken in the form of interviews with the community and city government and environmental observations. The results of this study show that the Medan Berkah collaboration has been well implemented but has yet to be fully effective in overcoming the waste problem in Medan City.